Bathroom ergonomic for the elderly / Dianna Nur A’ain Saidi - Saidi, Dianna Nur A’ain (2021)
Bathroom is very important room for everyone in their life. Personal basic needs of activities for human hygiene-healthcare such as brushing teeth and hair, bathing, defecate urination and even make up are using this important room called bathroom. Elderly people has their limitation of doing activities and movement. Sometimes, it may have a tendency to an accident. While, toilet or bathroom had become a high risk for fall and injuries to occur in a house. Likewise, fall injuries in bathroom ergonomic design were twice more than likely to result an injury. The aim of this study is to investigate and determine the bathroom ergonomic aspect and user satisfaction of bathroom design for elderly in Malaysia terrace house/link house. This research executed a mixed method research in which include pictogram observation and questionnaire survey methodology. Secondary data collected were collected by someone who is not an actual user. For example including magazines, books, newspaper and journals that are already available and analyse previously were also use in this research. This research and study are limit to the link house near Puncak Alam area due to the restriction that need to be follow due to stay at home rule by Malaysia’s government due to covid-19 pandemic and the scope of house is only been focused on terrace/link house only focusing on the bathroom fitting and finishing of the user existing bathroom based on the questionnaire distributed.